Pelatihan Fotografi dan Digital Marketing untuk Meningkatkan Penjualan Secara Online Mahasiswa Kalimantan Utara dan UMKM di Kelurahan Maleer Kota Bandung - Rosmayati, Siti; Maulana, Arman; Aksan Halim, K Prihartono; Handari Adji, Widwi; Paryanti, Dini; Yuliansyah Kusnadi, Dwi (LPPM Politeknik Piksi Ganesha, 2024)
This community service program was held with the aim of improving the skills of students and Micro, Small and Medium Enterprises (MSMEs) in Maleer Village, Bandung City, in utilizing product photography and digital marketing strategies to support online sales. The training was attended by 67 participants, consisting of the Taruna Class (20 participants), Regular Class (25 participants), Student Association (10 participants), Student Executive Board Delegation (7 participants), and staff (5 participants). The training materials included the basics of digital marketing, product photography techniques, and buying and selling practices on the TikTok and Meta Ads platforms (Facebook and Instagram Ads). The evaluation results showed a significant increase in participants' understanding of digital marketing strategies and their ability to produce attractive visual content. This program is expected to be able to increase the competitiveness of MSMEs in the digital era and enrich students' knowledge of digital marketing, so that it can have a positive impact on increasing product sales online.